Regional Priorities Of International Agriculture Integration Of Ukraine - Reznik Nadiia, Fedun Igor, Kudirko Ludmyla, Lezhepokova Victoriia, Oleinikov Yuriy (International Journal of Advanced Science and Technology, 2020)
The article explores the regional priorities of Ukraine’s participation in international integration processes. Its status as a party to the integration agreements has been identified. The potential of the agribusiness sector for deeper integration into international economic relations has been revealed. The results of the analysis have highlighted an important focus of the integration of the agro-industrial sector in the EU markets. The stages and key characteristics of Ukraine’s integration path are highlighted. Perspective sectoral priorities of Ukrainian agri-food exports for the selected foreign market have been identified. The variability of the consequences of the chosen integration path is revealed in the measurement of opportunities and risks because of the deepening of EU integration cooperation with the MERCOSUR countries. Further analysis needs a problem of the potential transformation of the structure of supply for export of agro-food products taking into account changes in the structure of land assets of Ukraine as a result of lifting the embargo on trade in agricultural land and corporate goals of new owners of land resources.